2013 IEEE Third Joint International Conference on Development and Learning and Epigenetic Robotics (ICDL) 2013
DOI: 10.1109/devlrn.2013.6652527
|View full text |Cite
|
Sign up to set email alerts
|

An Enactive approach to autonomous agent and robot learning

Abstract: A novel way to model an agent interacting with an environment is introduced, called an Enactive Markov Decision Process (EMDP). An EMDP keeps perception and action embedded within sensorimotor schemes rather than dissociated. Instead of seeking a goal associated with a reward, as in reinforcement learning, an EMDP agent is driven by two forms of self-motivation: successfully enacting sequences of interactions (autotelic motivation), and preferably enacting interactions that have predefined positive values (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Olivier Georgeon has several works on RL and the Enactive approach, [19,20] to cite few, but only in [14] he addresses the enactive paradigm. In [14] Georgeon, Wolf and Gay successfully apprehend the Enactive concept. The work does a good contribution to the Enactive field in putting the agent in a more active role in the sensorimotor loop.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Olivier Georgeon has several works on RL and the Enactive approach, [19,20] to cite few, but only in [14] he addresses the enactive paradigm. In [14] Georgeon, Wolf and Gay successfully apprehend the Enactive concept. The work does a good contribution to the Enactive field in putting the agent in a more active role in the sensorimotor loop.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a representative one from the group of related works and will present next. There is one work by Rafik Hadfi [13] we found that talks about enactivism and uses the work of Olivier Georgeon et al [14] (discussed next) to run an experiment, but Hadfi is much more interested in comparing Enactive Learning with Reinforcement Learning than making any contribution to advance enactivism, and his work fails to address fundamental points of enactivism. Before discussing the works of implementation we talk about another work that is similar to ours and we state the differences.…”
Section: Enactive Ai Implementationsmentioning
confidence: 99%
See 2 more Smart Citations
“… Video 2 (https://youtu.be/t1RO5S4mBEY) demonstrates the same algorithm implemented in an e-puck robot (Georgeon, Wolf & Gay 2013).  Video 3 (https://youtu.be/91kKzybt8XY) demonstrates the same algorithm used to control distal motorsensory schemes (Georgeon, Cohen & Cordier 2011).…”
Section: Examplesmentioning
confidence: 99%